Technical Efficiency of Digital and Non-Digital Banks in Indonesia: A Data Envelopment Analysis (DEA) Approach for the 2024–2025 Period - Ichwani, Tia; Nisa, Chaerani; Sinuraya, Murtada; Saputra, Deni Achmad (Dinasti Publisher, 2026)
This study aims to analyze the efficiency of digital and conventional banks in Indonesia using the Data Envelopment Analysis (DEA) method and examine the effects of bank size, digitalization, and credit risk on efficiency. The data covers eight digital banks and eight conventional banks during the 2024–2025 period, with input variables: labor costs, total assets, and operational costs; and output variables: interest income, third-party funds (TPF), and total disbursed credit. The analysis results show that digital banks have a higher average efficiency level (0.91) than conventional banks (0.83). Bank size has a significant positive effect on efficiency, while digitalization and credit risk (NPL) have a negative effect. These findings emphasize the importance of business scale and risk management in maintaining banking efficiency in the digital era.